Franco Stella. Nuovo Castello di Berlino - Bosi, Roberto (Firenze Architettura, 2021)
To trace back the history of the Berlin Castle from its foundation to the present day is like making an incursion into the political and urban history of the city it represents, in which the act of reconstruction becomes the moment of re-appropriation, on the one hand, of the ‘evocative efficacy’ of the Castle and, on the other, of the rediscovery of the special relationship that once connected the monument to the city and was later lost. The urban mission of the work and the fact of its being a monument lie at the centre of Franco Stella’s project.